MANDATORY PERFORMANCE OF THE PUBLIC PROSECUTOR'S OFFICE IN THE INCIDENT OF RESOLVING REPETITIVE DEMANDS - Bimbato Vieira, Victória (Revista Gênero e Interdisciplinaridade, 2021)
Representing a milestone in the evolution of Brazilian Law, the Federal Constitution of 1988 – known as the Citizen Constitution – assured the Public Prosecutor's Office the constitutional status of fiscal of the legal order, aimed at defending homogeneous individual, collective and diffuse rights. With the enactment of the 2015 Code of Civil Procedure, we had a new phase in the evolution of national law with the progress of the system of binding precedents in our legal system. The new normative diploma, following the Brazilian Magna Carta, brought a more present role of the Public Ministry in Procedural Law, including in the system of precedents. Within this system, one of the biggest innovations is the Repetitive Claims Resolution Incident, which aims to ensure isonomy and legal security in Brazilian legal processes. Thus, the question arises, why the legislator of the new Code of Civil Procedure guaranteed the mandatory action of the Public Prosecutor's Office in the Repetitive Claims Resolution Incident?